2021
DOI: 10.1002/jcb.30141
|View full text |Cite
|
Sign up to set email alerts
|

Distinct types of amyloid‐β oligomers displaying diverse neurotoxicity mechanisms in Alzheimer's disease

Abstract: Soluble oligomers of amyloid-β (Aβ) are recognized as key pernicious species in Alzheimer's disease (AD) that cause synaptic dysfunction and memory impairments. Numerous studies have identified various types of Aβ oligomers having heterogeneous peptide length, size distribution, structure, appearance, and toxicity. Here, we review the characteristics of soluble Aβ oligomers based on their morphology, size, and structural reactivity toward the conformationspecific antibodies and then describe their formation, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 135 publications
0
10
0
Order By: Relevance
“…Moreover, many reports indicated that the amount of soluble Aβ aggregates correlated much better with the severity of cognitive deficits than that of Aβ fibrils. Therefore, soluble Aβ aggregates are increasingly drawing attention as the therapeutic target , and a novel biomarker of AD. However, because soluble Aβ aggregates are diverse and transient, , the most toxic form of soluble Aβ aggregates is controversial, , and various toxic forms of soluble Aβ aggregates may exist in AD brains at the same time. , Hence, it is expected that the development of imaging probes for simultaneous in vivo detection of diverse soluble Aβ aggregates will contribute to the elucidation of the pathophysiology of AD, assessment of therapeutic agents for AD, and accurate diagnosis of AD in the early phase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many reports indicated that the amount of soluble Aβ aggregates correlated much better with the severity of cognitive deficits than that of Aβ fibrils. Therefore, soluble Aβ aggregates are increasingly drawing attention as the therapeutic target , and a novel biomarker of AD. However, because soluble Aβ aggregates are diverse and transient, , the most toxic form of soluble Aβ aggregates is controversial, , and various toxic forms of soluble Aβ aggregates may exist in AD brains at the same time. , Hence, it is expected that the development of imaging probes for simultaneous in vivo detection of diverse soluble Aβ aggregates will contribute to the elucidation of the pathophysiology of AD, assessment of therapeutic agents for AD, and accurate diagnosis of AD in the early phase.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in early Alzheimer’s disease human samples and in an amyloid precursor protein mouse model, it has been shown that the expression of orthologs of fz (FZD1 and FZD7) in the hippocampus was altered (Palomer et al ., 2022). The fz receptors were also implicated in the mechanism whereby soluble Aβ oligomers resulted in cognitive decline (Madhu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Aβ oligomers cause apoptosis, which finally results in neuronal death (Madhu & Mukhopadhyay, 2021). Therefore, prevention of neuronal apoptosis is considered to be a therapeutic strategy for AD.…”
Section: Discussionmentioning
confidence: 99%
“…In AD brains, Aβ monomers aggregate into oligomers, protofibrils, and insoluble amyloid fibrils (Michaels et al, 2020). Soluble Aβ oligomers exert deleterious effects in AD, and Aβ 42 oligomers are considered especially neurotoxic (Madhu & Mukhopadhyay, 2021). The NMDAR antagonist memantine, at proper concentration, preferentially blocks pathologically‐stimulated extrasynaptic NMDARs over physiologically‐activated synaptic NMDARs, and partially ameliorates Aβ‐induced synaptic toxicity and cognitive deficit (Tu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%